EVOLUTION OF DOMESTIC BANKING BUSINESS AND ITS LEGAL REGULATION IN THE XVII-XX CENTURIES - G. U. Atayan; O. N. Amvrosova (Гуманитарные и юридические исследования)
The article analyzes various aspects of the legal regulation of banking in XVII-XX centuries with the reference to modern, highly informative methods.The authors note that in the period under review, there was constant development and improvement of legal norms that regulate the activities of credit institutions, which determines the need rapidly developing economy of the country in many ways. Economic development was accompanied by increase in the number and the emergence of new types of credit institutions, which was inextricably linked with the adoption of new legislation.